Head count [videorecording (DVD)] - Burghart, Ben; Burghart, Jacob; Doke, Josh; Jakubenko, Aaron, 1988-; Zanetti, Melanie; Dyck, Kyle; Banks, Polaris; Bylsma, Chris; Schultz, Cinnamon; Kwanten, Ryan, 1976- (Shout! Factory, 2023)
An escaped convict has his own gun pointed at his head, desperate to remember what happened to each bullet as the empty rounds click away, he also needs to come up with an escape plan before a full chamber is fired by his unknown assailant.